Why do female athletes face harassment and bullying? A mixed-methods study - Ekowati; Edi Setiawan; Habibie; Khairul Hafezad Abdullah; Novri Gazali; Martin Hofmeister; Zsolt Németh (UIR Press, 2023)
The phenomenon of escalating harassment and bullying of female athletes in sports demonstrates that there is a gap and urgency for further scrutiny. This study aims to reveal harassment and bullying cases against female athletes in sports. This study applied a mixed method. Participants in this study were athletes in several sports organizations at the University of Islam 45 Bekasi (n = 30). A questionnaire was used as the quantitative research instrument to measure harassment and bullying in athletes, while in-depth interviews were used as the qualitative research instrument. Quantitative statistical analysis used IBM SPSS to find frequency and percentage, and qualitative analysis used thematic analysis. The quantitative research results significantly proved that all participants often experience harassment and bullying, with the highest rate occurring in gymnastics, swimming, volleyball, and soccer. While the results of the qualitative research showed that all participants had experiences or stories about harassment and bullying, the causal factors included the conditions of the training environment, athletes' clothes, attitudes, and the knowledge of coaches and athletes. In addition, participants stated that harassment and bullying negatively impact their health and psychological aspects. As a result, we emphasize that incidents of harassment and bullying occur frequently in female athletes while they are participating in sports. It is expected that this research could provide information and understanding to all sports practitioners in Indonesia and all countries in the world that harassment and bullying are very dangerous and immoral and must be handled as soon as possible by providing strict rules.